Insurance of real estate with assignment of rights as a security for mortgage loan repayment in the context of interests of consumers - Nowak, Katarzyna (Journal of Finance and Financial Law, 2019)
Lending by banks is fraught with credit risk which can be defined as a risk of default of the borrower. For this purpose banks require collateral especially insurance specifically insurance of real estate. Borrowers are also exposed to various types of risks which may make difficult to repay the loan in the future. In this connection borrowers can also benefit from insurance in the hope that insurer will repay the debt within insurance protection. In the article author presents the impropriety occurring in practice at the insurance of real estate distribution and assesses the main conditions assignment of rights to the bank.